Physiological and Comparative Transcriptomic Analysis Provide Insight Into Cotton (Gossypium hirsutum L.) Root Senescence in Response - Zhu, Lingxiao; Liu, Liantao; Sun, Hongchun; Zhang, Yongjiang; Zhu, Jijie; Zhang, Ke; Li, Anchang; Bai, Zhiying; Wang, Guiyan; Li, Cundong (Frontiers in Plant Science, 2021)
Nitrogen deficiency is one of the pivotal environmental factors that induce leaf senescence. However, little is known regarding the impact of low nitrogen on root senescence in cotton. In this study, the molecular mechanism of cotton root senescence in response to nitrogen deficiency was investigated by combing physiological and transcriptomic analysis. Nitrogen starvation induced the premature senescence of cotton aboveground, while delaying root senescence. The increase in catalase activity at 60, 80, and 100 days after emergence (DAE), combined with the decrease of malonaldehyde content at 60, 80, and 100 DAE, these results may be related to the delay of root senescence by low nitrogen treatment. To study the molecular mechanisms underlying root senescence, the gene expression profiling between low nitrogen and normal nitrogen treatments were compared pairwise at 20, 40, 60, 80, and 100 DAE. A total of 14,607 genes were identified to be differentially expressed at these five points. Most genes involved in glutathione and ascorbate peroxidase synthesis were upregulated, while abscisic acid, apoptosis, caspase, and cell cycle-related DEGs were downregulated. Coupled with the physiology data, these results provide new insights into the effect of nitrogen starvation on root senescence.